Strategi Sekolah Dalam Mempertahankan Kualitas Lulusan Siswa Pada Masa Pandemi Covid-19 di SMA Negeri 1 Padang - Muhammad Rafli Riyadi; Reno Fernandes; Ayu Adriyani (Naradidik: Journal of Education and Pedagogy, 2022)
The pandemic began to occur in early 2020. Due to the pandemic, education was conducted online. This raises several problems ranging from the difficulty of schools in adapting to even causing students to experience difficulties in learning and resulting in learning loss which makes the quality of school graduates experience a decline in quality. Therefore, this study looks at the strategy of SMA Negeri 1 Padang in maintaining the quality of graduates during the Covid-19 pandemic. This research was analyzed using a qualitative approach with the type of case study research. The informant selection technique in this study used a purposive sampling technique with a total of 7 informants consisting of school officials such as school principals, curriculum representatives, student representatives, counseling teachers, teaching teachers, and several students. Data collection techniques were carried out by direct observation to the research location, namely SMAN 1 Padang, interviewing informants in the field by asking several questions about the problems the authors faced and doing documentation. Data analysis techniques used in this study are data reduction, data presentation, data verification from Miles and Huberman. The validity of the data is done by data triangulation. The theory used in this research is the structural-functional theory from Talkott Parsons with the A.G.I.L (Adaptation, Goal, Integrity, and Latency) scheme. This theory views society as a unified system that functions with each other. If one system in society does not function properly, then the other system will experience problems. The results of this study are SMA Negeri 1 Padang is able to maintain the quality of graduates during online learning by using several strategies in implementing the online learning process so that learning can run with school quality standards so that school graduates are able to graduate to the most favorite PTN in Indonesia.